Impact of bedroom light exposure on glucose metabolic markers and the role of circadian-dependent meal timing: A population-based cross-sectional study - Qi Li; Yu-xiang Xu; Xiu-zhen Lu; Yu-ting Shen; Yu-hui Wan; Pu-yu Su; Fang-biao Tao; Xin Chen; Ying Sun (Ecotoxicology and Environmental Safety)
Background: Light at night (LAN) has become a global concern. However, little is known about the effects of bedroom LAN exposure on glucose metabolism markers. We aimed to explore the association between intensity and duration of bedroom LAN exposure with glucose metabolism markers, and the role of circadian-dependent meal timing in these associations. Methods: Real-ambient bedroom LAN exposure was measured using a portable illuminance meter for two consecutive days. Seven consecutive days of sleep time and 24-h dietary records were assessed by wrist-worn accelerometer and mobile phone photos, respectively. Circadian-dependent meal timing, including the timing of meal relative to clock time and sleep time, was calculated from 24-h dietary records and sleep data. Results: The mean age of participants was 18.7 years, and 32.8 % were male. Per SD lx increase of bedroom LANavg was associated with 1.75 μU/mL-increase in INS (95 %CI: 0.10, 2.50), 0.61 unit-increase in HOMA-IR (95 %CI: 0.43, 0.79), and 0.09 unit-increase in TyG (95 %CI: 0.04, 0.15); per SD min increase of bedroom LAN3 was associated with 1.61 μU/mL-increase in INS (95 %CI: 0.84, 2.37), 0.48 unit-increase in HOMA-IR (95 %CI: 0.29, 0.67), and 0.07 unit-increase in TyG (95 %CI: 0.01, 0.13). Nevertheless, these associations were found to be significant in later circadian-dependent meal timing group while weaker or not significant in earlier circadian-dependent meal timing group (time of first meal ≤ 9:00, time of last meal ≤ 19:00, first meal - sleep end ≤ 2 h, and sleep onset - last meal ≥ 5 h). Conclusions: Overall, bedroom LAN exposure was associated with impaired glucose metabolism markers among young adults. Importantly, circadian-dependent meal timing may have potentially moderate effects on these associations. Keeping bedroom darkness at night and adhering to early eating pattern may be important public health strategies to reduce the risk of glucose metabolism disorders.